Transforming Nursing Education: The Role and Impact of Augmented and Virtual Reality Training - Chaturvedi, Sakshi; Chaturvedi, Chakrapani (Medicine and Medical Research: New Perspectives Vol. 5, 2024)
Augmented reality (AR) and virtual reality (VR) are technologies that enhance the perception of reality by superimposing computer-generated images, sounds, or other sensory enhancements on a user's real-world environment. AR and VR training in medical education is crucial as it allows students to practice complex procedures in a safe and controlled environment, improving their skills and confidence. AR and VR training in nursing education has shown promise in memory retention, independent learning, critical thinking, decision-making, skill development, better patient outcomes, and job satisfaction. However, challenges such as potential motion sickness, difficulty adapting to the virtual environment, and the need for additional training are still present. Nurse educators face challenges such as the cost of implementing the technology, the need for ongoing technical support, and the time required to develop and maintain high-quality virtual simulations. Despite these challenges, the use of AR and VR in nursing education shows great promise in enhancing learning experiences and improving patient outcomes.